Injection of mineral dust into the free troposphere during fire events observed with polarization lidar at Limassol, Cyprus - Nisantzi, Argyro; Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Hadjimitsis, Diofantos G. (My University, 2014)
Four-year observations (2010–2014) with EARLINET polarization lidar and AERONET sun/sky photometer at Limassol (34.7° N, 33° E), Cyprus, were used to study the soil dust content in lofted fire smoke plumes advected from Turkey. This first systematic attempt to characterize less than 3-day-old smoke plumes in terms of particle linear depolarization ratio (PDR), measured with lidar, contributes to the more general effort to properly describe the life cycle of free-tropospheric smoke–dust mixtures from the emission event to phases of long-range transport (> 4 days after emission). We found significant PDR differences with values from 9 to 18% in lofted aerosol layers when Turkish fires contributed to the aerosol burden and of 3–13 % when Turkish fires were absent. High Ångström exponents of 1.4–2.2 during all these events with lofted smoke layers, occurring between 1 and 3 km height, suggest the absence of a pronounced particle coarse mode. When plotted vs. travel time (spatial distance between Limassol and last fire area), PDR decreased strongly from initial values around 16–18% (1 day travel) to 4–8% after 4 days of travel caused by deposition processes. This behavior was found to be in close agreement with findings described in the literature. Computation of particle extinction coefficient and mass concentrations, derived from the lidar observations, separately for fine-mode dust, coarse-mode dust, and non-dust aerosol components show extinction-related dust fractions on the order of 10% (for PDR =4%, travel times > 4 days) and 50% (PDR =15%, 1 day travel time) and respective mass-related dust fractions of 25% (PDR =4%) to 80% (PDR =15%). Biomass burning should therefore be considered as another source of free tropospheric soil dust.
Keywords: Soil dust; Troposphere; Fire events; Limassol; EARLINET polarization lidar; AERONET sun/sky photometer